Education and Society: A Social System - Bintang R. Simbolon (ijd-demos, 2022)
AbstractEducation and society have reciprocal relations. Reciproca relations this philosophical sociological explained in and in terms of their respective roles and the pedagogical described. Stratification of affecting the community has the educational process; next has a role in own education stratification while the effect on the system. Essentially system and education and stratification of the community have each other; integral relations communities are a unified system that is interdependent and have and education to adapt the continuous social development. Following a community, teaching to be elected by the people in education, giving ability in technologically functional, individual, then informative and open, and the knowledge in ethical and moral that may be developed through religion.Keywords: Society, Education, Social Change AbstrakPendidikan dan masyarakat memiliki hubungan timbal balik. Hubungan timbal balik sosiologis filosofis ini dijelaskan dalam dan dari segi peran masing-masing dan dijelaskan secara pedagogis. Stratifikasi yang mempengaruhi masyarakat memiliki proses pendidikan; selanjutnya memiliki peran dalam stratifikasi pendidikan sendiri sedangkan pengaruhnya terhadap sistem. Pada hakekatnya sistem dan pendidikan serta stratifikasi masyarakat saling memiliki; hubungan integral masyarakat adalah satu kesatuan sistem yang saling bergantung dan memiliki serta pendidikan untuk mengadaptasi perkembangan sosial yang berkesinambungan. Mengikuti komunitas, mengajar untuk dipilih oleh rakyat dalam pendidikan, memberikan kemampuan secara teknologis fungsional, individual, kemudian informatif dan terbuka, dan pengetahuan etika dan moral yang dapat dikembangkan melalui agama.Kata kunci: Masyarakat, Pendidikan, Perubahan Sosial